2021
DOI: 10.2298/vsp191122147m
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dentists’ knowledge about the use of radiology in pediatric dentistry in Serbia

Abstract: Background/Aim: Radiology is a crucial part of dentists' everyday practice. It plays a vital role in diagnosis, treatment planning and for follow-up care of patients. The aim of this study was to evaluate knowledge of dentists in Serbia concerning the use of radiology in pediatric dentistry.Methods: 252 dentists from across Serbia participated in the study. A questionnaire was created in order to examine dentists' knowledge towards using radiology in pediatric dentistry. The questionnaire consists of 39 questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…3 Although there are few survey studies on the subject, none of these studies drew attention to the use of radiography in the right indications by reference to the guideline. 7,8 As a result, in this study, we aim to explore this issue in depth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Although there are few survey studies on the subject, none of these studies drew attention to the use of radiography in the right indications by reference to the guideline. 7,8 As a result, in this study, we aim to explore this issue in depth.…”
Section: Discussionmentioning
confidence: 99%
“…stated that their second choice for caries detection and diagnosis is periapical radiography. 8 While only bite-wing radiography is recommended for caries diagnosis and monitoring; in the presence of additional pathology, periapical radiographs and in cases where the patient can not tolerate intraoral radiographs panoramic radiographs are recommended. 3 Due to the high proportion of dentists who choose panoramic radiograpy as their first option, it can be concluded that there is a lack of knowledge about the radiographic technique preferred by pediatric dentists in the detection and diagnosis of caries.…”
Section: Discussionmentioning
confidence: 99%